Heart or Mind? The Impact of Power Distance Belief on the Persuasiveness of Cognitive Versus Affective Appeals in Education Marketing Messages - Tu, Lingjiang Lora; Kwon, JaeHwan; Gao, Huachao (Journal of Marketing Research, 2022)
One of the greatest challenges in education marketing is designing effective marketing messages, especially when targeting consumers with different cultural backgrounds. This research examines the impact of power distance belief (PDB) on the persuasiveness of affective appeal versus cognitive appeal in education marketing messages. The authors theorize that low-PDB consumers tend to prefer education products presented with affective appeal because of their process learning mindset, which focuses on self-discovery and self-development. By contrast, high-PDB consumers tend to prefer education products presented with cognitive appeal because of their outcome learning mindset, which focuses on acquiring skills and social/economic gains relevant to such skills. These effects were supported by converging results from four experiments, a field study, and a content analysis across 37 countries using a wide range of education products and services. This research contributes to the literature on PDB, education, and cross-cultural consumer behavior and provides guidelines for global education marketers.